Proposal of an alternative upper divertor in ASDEX Upgrade supported by EMC3-EIRENE simulations. (August 2017) - Lunt, T.; Zohm, H.; Herrmann, A.; Kallenbach, A.; Dunne, M.; Feng, Y.; Neu, R.; Wischmeier, M.; ,
Highlights: Design of an upgrade of the upper divertor for ASDEX Upgrade discussed. Several new configurations possible among them XD, SF +, LFS SF −, HFS SF − Several heat flux mechanisms identified to be verified experimentally. Abstract: We discuss the benefits of installing a pair of in-vessel coils with currents | Ifx | ≲ 50 kAt in the upper divertor of ASDEX Upgrade (AUG) to study a series of 'alternative' divertor configurations, like the Snowflake (SF) and the X-divertor (XD), that are currently considered as alternative solutions for the power exhaust problem. The possibility of operating the standard lower single-null (SN) and double-null (DN) would be preserved. Potential effects to reduce the peak parallel- and/or perpendicular heat flux are predicted from a simple geometrical-diffusive model as well as by numerical EMC3-EIRENE simulations for pure deuterium attached conditions with spatially constant diffusion coefficients. Beyond that a series of other potential transport- and radiation related heat flux mitigation effects are identified and could be studied experimentally with the modified upper divertor in the high-power divertor Tokamak AUG.